The Effect of L-Carnitine as an Adjuvant Supplement on Lipid Profile in Iraqi Diabetic Patients - Wessam M. Shiblawi; Sajida H.Ismael (College of Pharmacy University of Baghdad, 2017)
Diabetes is a complex set of diseases require continuous medical care, to control blood sugar and prevent complications is .The aim of this research is to determine the effect of administration of   L carentin to diabetics on the   lipid profile. The research was conducted on sixty diabetic patients were selected from endocrinology and diabetes center / Al-Rusafa, within selected criteria. The patients divided into 3 groups (control group of healthy people and two groups of patients with diabetes who were on metformin and glibenclamide, one group took a L  carnitine in a dose of 1000 mg twice daily and a group dealing with a placebo for a period of 3 months continuously). The study found that patients who took Lcarnitine, showed a significant reduction (p <0.05) in the triglyceride level, while no significant changes were observed in the level of cholesterol and HDL and LDL.  This study concluded that administration of L carentin improved the lipid profile in type-2diabetic patients. Key word:  Diabetes mellitus (DM), Dyslipidemia, l-carnitine (LC).